Energy : the basics - Schobert, Harold H., 1943- (New York : Routledge, Taylor & Francis Group, 2014)
'People rarely stop to think about where the energy they use to power their everyday lives comes from and when they do it is often to ask a worried question: is mankind's energy usage killing the planet? How do we deal with nuclear waste? What happens when the oil runs out? Energy: The Basics answers these questions but it also does much more. In this engaging yet even-handed introduction, readers are introduced to: - the concept of'energy' and what it really means - the ways energy is currently generated and the sources used - new and emerging energy technologies such as solar power and biofuels - the impacts of energy use on the environment including climate change Featuring explanatory diagrams, tables, a glossary and an extensive further reading list, this book is the ideal starting point for anyone interested in the impact and future of the world's energy supply. Harold Schobert is Professor of Fuel Science in the Department of Energy and Mineral Engineering at Penn State University. He is the author of Energy and Society 2nd Edition (CRC Press, 2011),'--
Includes bibliographical references and index.
Keywords: Power resources